A Novel Vaccine Candidate: Recombinant Toxoplasma gondii Perforin-Like Protein 2 Stimulates Partial Protective Immunity Against Toxoplasmosis - Tian, Xiaowei; Sun, Hanqi; Wang, Meng; Wan, Guangmin; Xie, Tong; Mei, Xuefang; Zhang, Zhenchao; Li, Xiangrui; Wang, Shuai (Frontiers in Veterinary Science, 2022)
Toxoplasma gondii is an apicomplexan pathogen infecting 2 billion people and numerous livestock, causing a major threat to economies and human health. Passive-active immunoprophylaxis is an efficient approach to provide protection against toxoplasmosis. T. gondii perforin-like protein 2 (TgPLP2) contains a membrane attack complex/perforin (MACPF) domain, making it a potential vaccine candidate. Here, we aimed to assess the protection efficacy of TgPLP2 using Bagg albino/c (BALB/c) mice model. The Escherichia coli system was used to obtain the recombinant TgPLP2 (rTgPLP2). Mice challenged by anti-rTgPLP2 polyclonal antibodies (PcAb) pretreated tachyzoites showed obviously increased survival outcomes. In addition, mice that passively received anti-rTgPLP2 PcAb following a lethal dose of tachyzoites infection had longer survival time compared with phosphate-buffered saline (PBS) controls. Furthermore, we demonstrated that immunization with rTgPLP2 could prolong survival in RH strain infected mice and resulted in the lowest brain cysts size and number of Prugniaud (PRU) genotype II strain infected mice. High levels of Toxoplasma-specific IgG, IgG1, IgG2a, and cytokines (IFN-γ and IL-10) were produced after two immunizations with rTgPLP2. Together these results indicated that TgPLP2 can induce both humoral and cellular immune responses to protect host against infection and thus is a potential candidate for T. gondii vaccines.